Conservative management of femoroacetabular impingement (FAI) in professional basketball - Salas, C.; Sintes, P.; Joan, J.; Urbano, D.; Sospedra, J.; Caparros, T. (Apunts Sports Medicine, 2020)
Femoroacetabular impingement (FAI) is a common injury in basketball, having a difficult therapeutic approach because it requires an extended period of time to be resolved once it appears. Therefore, preventing the onset of this condition seems critical in maintaining athletes` health, and availability to compete. Because reducing training and competition volume in a professional team context is complex, the exercises presented here offer a good option for managing injured players without compromising their availability during the season. However, offseason and preseason periods are key to developing, protecting and strengthening the injured joint and its functionality for the competitive season.